TATANAN UPACARA MEMBANGUN â€œPAUMAHANâ€ (Kajian Ritual Pembangunan Rumah Tinggal Tradisional Bali) - IDA BAGUS GDE MANUABA (Universitas Dwijendra, 2012)
In the context within developing for the traditional housing is not very complicated if we search its meaning related to find out the happiness for all, in realistic and religious term. All traditional housing development steps have to be followed by a specific process conducted by ritual activity, such as : nyakap palemahan, nasarin dan melaspas.Â Â Â Â Â Â Â Â Â Â Â The article is a library research by selecting some related literatures using content of analysis method. From the literatures above the similar content are confirmed and inducted and finally the conclusion is a categorization of contents.Â Â Â Â Â Â Â Â Â Â Â The result show that there are two items regarding research problem to be anwered, those are : (i) the step and way in the traditional process developing consist of : (i) ngaskara process and its offering, (ii) the offering gradual depends on the economical and social level.